The determinants of China’s outward foreign direct investment in ASEAN: A panel ARDL approach - Unggul Heriqbaldi; Naufira Deilya Mufiidah (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This paper aims to examine factors influencing China's outward foreign direct investment (FDI) in ASEAN economies.Design/Methodology/Approach: The Kao panel cointegration approach and the Panel ARDL model were used in this study to estimate the long-run and short-run relationship between variables. This method is deemed superior to other panel models since it is advantageous when dealing with non-stationary variables at the level or I(1).Research findings: The estimation results provide empirical evidence that in the long run, ASEAN market size, exchange rate, import and export levels between China and ASEAN countries, inflation rate, and institutional factors such as the index of corruption control and political stability are the primary determinants of the flow of outward foreign direct investments from China to ASEAN economies. Theoretical contribution/Originality: This study provides additional evidence regarding the factors influencing direct investment flow from the home country to the host country, known as an outward foreign direct investment (OFDI). Previous studies have robustly proven that OFDI flows are influenced by factors such as the resources and market size of the host country, as predicted by location theory. This study further provides evidence that host country trade policy, the level of competitiveness demonstrated by favorable exchange rates, and institutional factors like corruption control and political stability are other important determinants in the context of China’s OFDI in ASEAN countries.Practitioner/Policy implication: Maintaining open trade policy, a competitive exchange rate and significant improvement in law and order would be suitable policies for ASEAN economies to attract more investment from China and other countries.Research limitation/Implication: This study did not cover other variables, such as investment facilities provided by the host government. In addition, economic packages like tax holidays and import-tariff discounts are common policies ASEAN countries provide. Hence, this variable can be considered in future research.